2012
DOI: 10.1016/j.bbagen.2011.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillation of transferrin

Abstract: The nature of fibrillar deposits from aqueous solutions of human serum and recombinant human transferrin on mica and carbon-coated formvar surfaces has been investigated. Atomic force microscopy showed that the deposition of recombinant transferrin onto the hydrophilic surface of mica resulted in the formation of a monolayer-thick film composed of conformationally-strained flattened protein molecules. Elongated fibres

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Serotransferrin (TF) glycosylation (Taniguchi et al, 2008) and aggregation (Booyjzsen et al, 2012) may play an important role in the pathophysiology of AD and also modulate the homeostasis of full-length APP (Khachaturian, 2008). Secretory carrierassociated membrane protein 1 (SCAMP1) and AP2-associated protein kinase 1 (AAK1) decreases the TF uptake by endocytosis suggesting their role in endocytosis via a mechanism, which may involve the recruitment of clathrin coats to the plasma membrane and the transGolgi network (Fernandez-Chacon et al, 2000, Conner andSchmid, 2002).…”
Section: Relationships Of Chronic Cerebral Hypoperfusion Altered Synamentioning
confidence: 99%
“…Serotransferrin (TF) glycosylation (Taniguchi et al, 2008) and aggregation (Booyjzsen et al, 2012) may play an important role in the pathophysiology of AD and also modulate the homeostasis of full-length APP (Khachaturian, 2008). Secretory carrierassociated membrane protein 1 (SCAMP1) and AP2-associated protein kinase 1 (AAK1) decreases the TF uptake by endocytosis suggesting their role in endocytosis via a mechanism, which may involve the recruitment of clathrin coats to the plasma membrane and the transGolgi network (Fernandez-Chacon et al, 2000, Conner andSchmid, 2002).…”
Section: Relationships Of Chronic Cerebral Hypoperfusion Altered Synamentioning
confidence: 99%
“…However, TF is a high abundant protein in the plasma [20]. In present study, we applied human iPSC-derived cardiomyocytes model to evaluate the effect of TF.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been observed that transferrin can form fibrils under certain conditions in vitro , and this led to an investigation to determine whether transferrin has amyloid-like properties. Synchrotron X-ray circular dichroism (XCD) was used to test whether transferrin in solution has amyloid-like properties, and this helped show that transferrin aggregation in solution does not appear to involve major structural changes to the protein, or formation of beta-pleated sheets (Booyjzsen et al, 2012). …”
Section: Iron-binding Proteins and Aggregationmentioning
confidence: 99%